Analisis Klaster Emerging Adulthood Mengenai Pengaruh Perjalanan Wisata Terhadap Kualitas Hidup - Ramadhani, Alya Fitri; Rosita, Rosita; Marhanah, Sri (Jayapangus Press, 2025)
Travel plays a crucial role in shaping and influencing the quality of life of emerging adulthood who explore their lives. The motivation for travel is a pivotal factor that determines their view about the influence of travel on quality of life. This study focused on individuals aged 18 to 25 who had traveled at least once in the six years (2018-2024). A total of 212 respondents answered the questionnaires distributed to collect data.. The collected data underwent rigorous analysis using various methods, including descriptive statistics, validity and reliability tests, hierarchical cluster analysis, chi-square, and ANOVA. These analyses were conducted with the assistance of the SPSS Statistics version 23 program. The findings of this research indicated that travel has a significant effect on the quality of life of emerging adulthood. Applying cluster analysis to the survey data resulted in the identification of four distinct categories of respondents according to their views on the effects of travel. These categories are (1) the least affected cluster, (2) the cognitively affected cluster, (3) the socially affected cluster, and (4) the most affected cluster. The largest cluster, designated as